2012
DOI: 10.1378/chest.11-1880
|View full text |Cite
|
Sign up to set email alerts
|

Indium Lung Disease

Abstract: Indium is a relatively rare element that has had limited use for decades as a metal, in alloys, and for electronics applications. During the past 15 years, global demand for indium has increased several-fold, driven by the novel use of indium-tin oxide (ITO) thin fi lms in the production of fl at-panel displays (such as liquid crystal displays [LCDs]), touch screens, and other electronic devices. 1,2 ITO is a sintered ceramic material typically consisting of 90% indium oxide (In 2 O 3 ) and 10% tin oxide (SnO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
103
2
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 110 publications
(120 citation statements)
references
References 25 publications
9
103
2
6
Order By: Relevance
“…If pulmonary macrophages are injured and cannot perform their normal functions, phagocytosis of pathogens is reduced, leading to increased risk of infections. Furthermore, it is hypothesized that indium lung toxicity results in the accumulation of alveolar surfactant proteins due to macrophage dysfunction (Cummings et al, 2012). This is seen in pulmonary alveolar proteinosis, which is one of the main lung diseases seen in workers from the ITO industry (Cummings et al, 2010(Cummings et al, , 2012.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If pulmonary macrophages are injured and cannot perform their normal functions, phagocytosis of pathogens is reduced, leading to increased risk of infections. Furthermore, it is hypothesized that indium lung toxicity results in the accumulation of alveolar surfactant proteins due to macrophage dysfunction (Cummings et al, 2012). This is seen in pulmonary alveolar proteinosis, which is one of the main lung diseases seen in workers from the ITO industry (Cummings et al, 2010(Cummings et al, , 2012.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is hypothesized that indium lung toxicity results in the accumulation of alveolar surfactant proteins due to macrophage dysfunction (Cummings et al, 2012). This is seen in pulmonary alveolar proteinosis, which is one of the main lung diseases seen in workers from the ITO industry (Cummings et al, 2010(Cummings et al, , 2012. In addition to the consequences of cell death, it is possible that prior to a loss in viability, release of cytokines, and initiation of an inflammatory response might further damage the epithelium and propagate the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three cases of PAP from indium compounds have been described in the literature (Cummings et al 2010(Cummings et al , 2012Xiao et al 2010). In all 3 cases, PAP occurred within 1-2 yr after initial exposure.…”
Section: Indiummentioning
confidence: 99%
“…The radiographic data, using different methods, showed that in 2 patients with PAP a subsequent fibrosis developed. The authors suggested that this disease may begin with PAP and progress to include fibrosis (Cummings et al 2012).…”
Section: Indiummentioning
confidence: 99%